High-Resolution Environmagnetic Study of HOTRAX Core JPC-14 from the Alpha Ridge, Arctic Ocean - Wang, Yanwei (The University of Bergen, 2007)
Core JPC-14 was derived from the HLY-0503 expedition from the Alpha Ridge. My supervisor professor Reidar Løvlie guided me with the project, from experiments, data obtaining, and analyisis. Master i Geovitenskap - Kvartærgeologi og paleoklima MAMN-GVKVA GEOVKVAR